Experimental Methods for the Quantitative Assessment of the Volume Fraction of Movable Shale Oil: A Case Study in the Jimsar Sag, Junggar Basin, China - Luo, Xia; Zhao, Zhongying; Hou, Lianhua; Lin, Senhu; Sun, Feifei; Zhang, Lijun; Zhang, Yan (Frontiers in Earth Science, 2021)
Deep insights into the movability of the retained shale oil are of great significance to shale oil. Rock and crude oil samples were collected from well J174 in the Jimsar Sag, Junggar Basin. Rock samples were subjected to different extraction followed by analysis of the component in the extracts, and measurement of porosity in conjunction with nuclear magnetic resonance and high-pressure mercury injection analysis. The results of these analyses were used to establish an experimental method for quantitative assessment of movable shale oil. The extract content of the component varied among different extraction and between mud shale and non-mud shale samples. The saturated hydrocarbon in the extracts of the mud shale was similar to those of the non-mud shale after extraction with CHCl3 alone or after sequential extraction with nC6+CHCl3. The aromatic hydrocarbon in the extract were significantly lower for the mud shale than for the non-mud shale after extraction with nC6, but the opposite was observed after sequential extraction with nC6+CHCl3. The contents of the non-hydrocarbon in the extract were significantly lower for the mud shale than for the non-mud shale after extraction with nC6, but the opposite was observed after extraction with CHCl3 or nC6+CHCl3. The contents of the asphaltene in the extract were not significantly different for the mud shale and non-mud shale after extraction with nC6, but the contents were higher for the mud shale than for the non-mud shale after extraction with nC6+CHCl3 or CHCl3. The viscosity of the crude oil was negatively correlated with the saturated hydrocarbon, was positively correlated with the aromatic hydrocarbon and non-hydrocarbon, and was not correlated with the asphaltene. For the mud shale and non-mud shale, their porosity after extraction with nC6 or CHCl3 was higher than their original porosity. Moreover, their porosity after extraction with CHCl3 was higher than after extraction with nC6. The movable oil was significantly correlated with the lithology, with sandstone allowing for a higher fluid movability than mud shale and dolomite allowing for a higher fluid movability than siliceous rocks.